2008
DOI: 10.1172/jci35237
|View full text |Cite
|
Sign up to set email alerts
|

Constitutively active Akt1 expression in mouse pancreas requires S6 kinase 1 for insulinoma formation

Abstract: Factors that promote pancreatic β cell growth and function are potential therapeutic targets for diabetes mellitus. In mice, genetic experiments suggest that signaling cascades initiated by insulin and IGFs positively regulate β cell mass and insulin secretion. Akt and S6 kinase (S6K) family members are activated as part of these signaling cascades, but how the interplay between these proteins controls β cell growth and function has not been determined. Here, we found that although transgenic mice overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 52 publications
(80 reference statements)
3
52
0
Order By: Relevance
“…76 Uncertainties still remain as to (1) what are the underlying mechanisms and key downstream effector(s) by activation of AKT signaling, implicating this kinase in regulation of β-cell cell cycle progression. 91 Little is known about the signaling events downstream of S6K. The importance of ribosomal S6 protein was assessed using knock-in mice containing alanine substitutions at all five phosphorylatable serine residues of their S6 protein.…”
Section: How Decreased Akt Signaling By Mtorc1-mediated Negativementioning
confidence: 99%
“…76 Uncertainties still remain as to (1) what are the underlying mechanisms and key downstream effector(s) by activation of AKT signaling, implicating this kinase in regulation of β-cell cell cycle progression. 91 Little is known about the signaling events downstream of S6K. The importance of ribosomal S6 protein was assessed using knock-in mice containing alanine substitutions at all five phosphorylatable serine residues of their S6 protein.…”
Section: How Decreased Akt Signaling By Mtorc1-mediated Negativementioning
confidence: 99%
“…Several studies have shown that pharmacologic inhibition of mTORC1 can attenuate the growth of pancreatic cancer cell lines in vitro and in vivo (20)(21)(22), but the identity of downstream effectors remains largely unknown. S6K has been implicated in tumorigenicity (23) but not in the context of PDAC. S6K has multiple substrates, including rpS6, whose phosphorylation is tightly coupled to mTORC1 activity (24).…”
Section: Introductionmentioning
confidence: 99%
“…Because of its pivotal role in these processes, S6K has been recognized as a promising therapeutic target for a number of human cancers (10,12,14,15). Genetic and pharmacological suppression of the S6K pathway has been shown to prevent malignant transformation and block cancer progression (9,(15)(16)(17). However, recent reports have exposed some limitations to the singular targeting of the S6K pathway alone, as such approaches can primarily induce cell cycle arrest with minimal induction of cell death (10,18).…”
mentioning
confidence: 99%